Oxford reading tree: floppy's phonics level 1+. Book 2, I, n, m, d - Hepplewhite, Debbie; Hunt, Roderick Brychta, Alex (Oxford University Press Oxford, 2011)
Level 1+ Floppy's Phonics Sounds and Letters Books show all the sounds and graphemes from Phase 2 of Letters and Sounds in the context of Oxford Reading Tree scenes, packed with activities for practice and consolidation.